Tinjauan Tradisi Nasi Berkat Mayit di Desa Sei Mencirim Deli Serdang Perspektif Tafsir Al-Munir - Indah Salsabila Harahap; Hasan Bakti Nasution (CV Global Research Publication, 2026)
This study aims to analyze the construction of religious meanings embedded in the Nasi Berkat Mayit tradition in Sei Mencirim Village and to reconstruct the tradition from the perspective of Wahbah al-Zuhaili’s Tafsir al-Munir. This research employs a qualitative approach through field research within the framework of Living Qur’an studies. Data were collected through observation, in-depth interviews with 13 informants, and documentation. The collected data were analyzed using the interactive model of Miles, Huberman, and Saldana, combined with thematic Qur’anic interpretation of verses related to charity, social solidarity, and the principle of removing hardship in Islamic teachings. The findings reveal that the Nasi Berkat Mayit tradition consists of three interconnected dimensions: theological dimension as an expression of charity and prayer for the deceased, cultural dimension as a form of Javanese collective identity, and social dimension as a mechanism for strengthening community solidarity. Through the analysis of Tafsir al-Munir, this study argues that the tradition can be maintained as long as it fulfills three Qur’anic principles: al-birr (commitment to goodness), ta’āwun (cooperation in righteousness), and raf’ al-ḥaraj (the removal of hardship). This study proposes a maslahah-based reconstruction model through value selection, critical evaluation, and transformation of traditional practices to ensure their relevance within contemporary social conditions while preserving their Qur’anic substance. These findings contribute to Living Qur’an studies by demonstrating that the relationship between the Qur’an and local traditions operates through a dialogical process of negotiation and social reconstruction